Investigation of nitrate and nitrite concentration and other physicochemical parameters of drinking water sources in Saveh city during the year of 2018 - Hossein Azarpira; Tayebeh Rasolevandi; Rahim Aali; amirhossein mahvi; Mohammad Amin Ghorbanpour; hanieh moradi; Ali Atamaleki; Maryam Sadeghipour; Zahra Sarlak (Mashhad University of Medical Sciences, 2018)
Abstract   Background and Purpose:Qualitative parameters of drinking water such as concentration of nitrate, nitrite, sulfate, total soluble solids, sodium, magnesium, fluoride, total hardness and electrical conductivity can play an important role in groundwater resources and are mainly related to agriculture, waste disposal areas and sewage. The aim of this study was to determine these parameters in drinking groundwater resource of Saveh city using Geographic Information System during the year of 2018 and investigation of contaminant's in the region's aquifer. Materials and Methods:This research is a descriptive-analytic study. 120 samples of water from 12 drinking water wells were prepared in spring and two times in the morning and afternoon in different parts of the city of Saveh. The quality parameters of drinking water, including concentration of nitrate, nitrite, sulfate, total soluble solids, sodium, magnesium, fluoride, total hardness and electrical conductivity were entered into the GIS software and stored in a database and then processed by the information system software, color mapping was prepared and geographical maps (GIS) were mapped to qualitative status. Also, reverse interpolation was used to estimate the conditions of the whole region. Findings:The average concentration of chlorine, sulfate, electrical conductivity, total soluble solids, total hardness and sodium exceeds the permissible limits, and the non-qualitative water conditions are quite evident. Also, the amount of two magnesium and sulfate ions was above the standard 1053. It should be kept in mind that the high levels of these two ions can interfere with the digestive system. Fluoride and nitrate levels were also acceptable range in all areas. Conclusion:The highest deviation level from 1053 standard was for total soluble solids, sodium, magnesium, and sulfate. It is better to consider a comprehensive program to solve the problem, including use of nanotechnology, filtering or ion exchange.